Emosi konsumen dan ikatan merek sebagai mediasi antara nilai hedonik dan harga premium pada pelanggan makanan siap saji - Pandowo, Aditya; Pandowo, Merinda; Sumakul, Grace Christine (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2023)
The objectives of this study are to explore the antecedents of premium prices derived from the hedonic value of a product/service, consumer emotions and brand attachment, andÂ to explore the mediating role of consumer emotions, and brand attachment in the relationship between hedonic value and premium prices. A total of 155 respondents participated in this study using the purposive sampling method, and data analysis using the Smart-PLS module. The results show that consumer emotions, and brand attachment affect directly on consumersâ€™ willingness to sacrifice at premium prices. Additional findings point to a mediating role for consumer emotions and brand attachment in explaining the relationship between hedonic value and premium price. This shows the need for business entities to pay attention to these constructs as a driver for consumers to pay extra high so that the company's profitability is higher.